2022
DOI: 10.3390/molecules27031137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fast and Sensitive Proteome Profiling of FF and FFPE Kidney Patient Tissues

Abstract: The application of proteomics to fresh frozen (FF) and formalin-fixed paraffin-embedded (FFPE) human tissues is an important development spurred on by requests from stakeholder groups in clinical fields. One objective is to complement current diagnostic methods with new specific molecular information. An important goal is to achieve adequate and consistent protein recovery across and within large-scale studies. Here, we describe development of several protocols incorporating mass spectrometry compatible deterg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…There can be anywhere between 47-92% overlap of protein identification between FF and FFPE tissues 32,37,38 . Previous studies have sought to optimise individual steps in the sample preparation workflow, notably the deparaffinisation or the tissue solubilisation steps for FFPE samples 12,39 , the LC settings 40 or the type of MS fragmentation 15 .…”
Section: Discussionmentioning
confidence: 99%
“…There can be anywhere between 47-92% overlap of protein identification between FF and FFPE tissues 32,37,38 . Previous studies have sought to optimise individual steps in the sample preparation workflow, notably the deparaffinisation or the tissue solubilisation steps for FFPE samples 12,39 , the LC settings 40 or the type of MS fragmentation 15 .…”
Section: Discussionmentioning
confidence: 99%
“…2F). Compared with previous spatially resolved proteomic studies of LCM tissues 26,28 in which at least 0.5 mm 2 sized tissues were required to quantify >1000 proteins, 23,46 the LCM-HD-nanoPOTS system provided > 1000 quantifiable proteins from 0.01 mm 2 sized tissues, i.e. using a ~50-fold smaller tissue volume.…”
Section: Sensitivity Evaluation For the Hd-based Spatial Proteomics M...mentioning
confidence: 92%
“…47,48 To identify an optimal surfactant for spatial proteomics, we evaluated three commercially available and MScompatible surfactants, including DDM, ProteaseMax, and RapiGest (Table S2). RapiGest and ProteaseMax are widely used in low-input bottom-up proteomics studies, 46,49 as all have been demonstrated to improve protein solubility and tryptic digestion efficiency. They are also readily degraded under acidic condition, and thus are compatible with a single-tube preparation workflow.…”
Section: Optimal Surfactant For Spatial Proteomicsmentioning
confidence: 99%
“…2F). Compared with other spatially resolved proteomic studies of LCMderived tissues, 23,46 in which at least 0.5 mm 2 sized tissues were required to quantify >1000 proteins, the LCM-HD-nanoPOTS system provided >1000 quantifiable proteins from 0.01 mm 2 sized tissues, i.e. using a ∼50-fold smaller tissue volume.…”
Section: Sensitivity Evaluation For the Hd-based Spatial Proteomics M...mentioning
confidence: 99%
“…47,48 To identify an optimal surfactant for spatial proteomics, we evaluated three commercially available and MS-compatible surfactants, including DDM, ProteaseMax, and RapiGest (Table S2 †). RapiGest and ProteaseMax are widely used in low-input bottom-up proteomics studies, 46,49 as all have been demonstrated to improve protein solubility and tryptic digestion efficiency. They are also readily degraded under acidic condition, and thus are compatible with a single-tube preparation workflow.…”
Section: Optimal Surfactant For Spatial Proteomicsmentioning
confidence: 99%